Strategi Dakwah Lembaga Politik Islam dalam Mensyiarkan Agama Islam - Rhohis Kurniawan; Muhammad Firdaus; Muhammad Yakub (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Islamic political preaching has become an increasingly significant phenomenon in Indonesia's socio-political landscape. Islamic political institutions develop various da'wah strategies that are adaptive to changing times, ranging from traditional approaches to the use of digital technology. This study analyzes the various da'wah strategies implemented by Islamic political institutions in Indonesia in broadcasting the teachings of Islam. The results show that effective strategies include the integration of Islamic values in the political agenda, the use of social media as a means of da'wah, a moderation approach in political communication, and a systematic cadre program. The main challenge lies in maintaining a balance between da'wah and politics so as not to be trapped in the politicization of religion, while the biggest opportunity lies in developing a moderate Islamic narrative that is relevant to the Indonesian context.